Risk factors of leptospirosis incidence in agricultural area - Mitoriana Porusia; Annisa Fauziah Dwi Andari; Windi Wulandari; Duangruedee Chotklang (Intelektual Pustaka Media Utama, 2021)
The rate of leptospirosis incidence in Boyolali regency, Indonesia, during 2017 was high and showing an increasing trend. According to Boyolali District Health Office the number of leptospirosis cases in 2017 was 34 cases. Factors related to leptospirosis in the agriculture area should be understood well to take the right measurements for leptospirosis control in a typical agricultural area. Several risk factors, such as personal hygiene, environmental sanitation, wound presence, occupation, are the factors of leptospirosis infection. This study aimed to determine the risk factors associated with the leptospirosis incidence in Boyolali regency, Indonesia. This research used an observational method with a case-control design. The total number of case sample was 33 people, and the control sample were 99 people (ratio 1:3) with matched by a living area. Data collection were carried out with interviews using a questionnaire to respondents related to personal hygiene, environmental sanitation, wound presence and work as a farmer. The data were tested using logistic regression. Most of the case respondents work as a farmer and worker. The results showed that the risk factors associated with leptospirosis incidence were a wound presence (OR:17.014;95% CI:5.487-52.761) and worked as a farmer (OR:5,186; 95%CI:1.682-15.989). Unrelated variables were bad personal hygiene (95%CI:0.647-7.885) and environmental sanitation (95%CI:0.793-8.773). The dominant risk factor that causes Leptospirosis was wound presences and occupation as a farmer. Therefore people who work mostly touch the water like farmers must cover any wound on feet and keep personal and environmental sanitation to prevent infection.